Physiological Changes in Mother During Pregnancy that Impact on the Pharmacokinetics and Pharmacodynamic of Drug: Literature Review - Jesviekha Ardriani Maulana; Jesy Fatimah (PT FORMOSA CENDEKIA GLOBAL, 2023)
Physiological changes occurring during pregnancy can affect drug pharmacodynamics and pharmacokinetics, leading to decreased or increased drug disposition. This research uses a systematic review method or literature review. The analysis was carried out by collecting data that met the requirements and filtering based on the suitability of the article title with the research objectives to obtain relevant articles after going through the filtering stage to data extraction. The results showed that physiological changes in pregnancy induce major changes in the pharmacokinetic properties of many drugs. These changes affect the distribution, absorption, metabolism, and excretion of drugs, and thus may affect their pharmacodynamic properties during pregnancy.